From the Search for a Molecular Code of Memory to the Role of Neurotransmitters: A Historical Perspective - Georges Chapouthier (Neural Plasticity)
The history of the neurochemistry of mnesic processes can be divided into two main periods: the first (1946-1978) was inspired by the results of molecular genetics, providing evidence for storage of hereditary information in the DNA of genes. Therefore, the chemical bases for memory were investigated in the macromolecules of the brain. Such attempts were relatively unsuccessful, which led to a second period (starting in 1978) with the research emphasizing, in a less ambitious way, the role of the molecular correlates of mnesic processes, in particular in the main transmitter systems of the brain.